DOSAGE FORM DEVELOPMENT AND PRELIMINARY PHYSICOCHEMICAL CHARACTERIZATION OF TRIKANTAKADI KVATHA - Sharma, Swati; Baghel, Dileep Singh; Singh, Saurabh; Singh, Sachin Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: This is aimed to study the development of different dosage form and physicochemical characterization of Trikantakadi Kvatha (TK). Methods: Stability, shelf life, non-convenient, and large dosages administration are the major concern for Kvatha. To overcome these problems, an effort has been made to modify the formulation without changing its efficacy into various dosage forms such as tablet, syrup, and tincture. Comparative pharmacognostic, physicochemical, and phytochemical parameters of crude herbs and prepared formulations were investigated. TK was prepared by classical method mentioned in literature and converted into TK syrup, TK Ghana vati, and Trikantakadi tincture (TT). Precaution should be taken during the processing of formulations. TT placed at a dark place in airtight container. Results: Physicochemical and phytochemical investigations are not shown any remarkable variations with various prepared dosage forms. The Rf range observed between the 0.08 and 0.80 follows the standard value when compared with the reference of plant drug used for the preparation of dosage form. Conclusion: The prepared dosages forms were not exhibited any remarkable difference according to thin-layer chromatography studies and physicochemical parameters. However, the developed dosage forms are more stable than kvatha.